Man-machine interactions 5 : 5th International Conference on Man-Machine Interactions, ICMMI 2017 held at Kraków, Poland, October 3-6, 2017 /: 5th International Conference on Man-Machine Interactions, ICMMI 2017 held at Kraków, Poland, October 3-6, 2017. ([2018]) - Unknown
No abstract available